Early Stunting Detection Education as an Effort to Increase Mother's Knowledge about Stunting Prevention - Sari, Gadis Meinar (Folia Medica Indonesiana, 2021)
Stunting is one of the main nutritional problems that is still common in children under five and has serious health impacts. The results of National Health Research (Riskesdas) in 2018 showed the prevalence of stunting at 30.8%, indicating that 1 out of 3 Indonesian children are still stunted. Probolinggo Regency is a priority area for stunting handling in 2019 with a prevalence of 50.2% according to a report from the National Team for the Acceleration of Poverty Reduction (TNP2K). One of the factors that directly affect the incidence of stunting is low birth weight (LBW), while the mothers' knowledge level of health is an indirect factor that affects the growth conditions of children under five. The purpose of this study was to analyze the effect of providing stunting early detection education on maternal knowledge regarding stunting prevention. This is a pre experimental research study with one group pre-post test design, children aged 0-24 months as the research subjects. The case group consisted of stunted children (BL/A <-2 SD Z-score), while the control group consisted of normal children according to the BL/U indicator. The number of research subjects for the case and control groups was 40 with mothers of the toddlers as research respondents. The samples were selected using total sampling technique. Data were analyzed using dependent T test and linear regression. The results suggested that at the beginning of the session before provided education about early detection of stunting, mothers with stunting toddlers had lower level of knowledge (73.3%) than those with normal toddlers (77%). After provided with education, the knowledge level of mothers with stunted toddlers appreared to be higher (89%) than those with normal children (87.6%), with significant increase in each group (P <0.05). It can be concluded that education on stunting detection can significantly improve mothers' knowledge regarding the prevention of stunting in children aged 0-24 months. Providing regular education, both by nutrition workers at the health center and integrated service post (posyandu) cadres, is necessary as an effort to prevent stunting to the maximum.